Charge-pumping studies of hot-carrier effects in submicrometer PMOSFETs - Ang, Chew Hoe (2009)
In this study, a constant amplitude charge-pumping (CP) measurement system was successfully setup. This system was used to analyse hot-carrier effects in submicrometer p-channel MOSFETs (metal-oxide-semiconductor field effect transistor) during hot-carrier stress and after termination of hot-carrier stress.